Cytotoxic New Nortriterpene from Roots of Potentilla atrosanguinea var. argyrophylla and its UPLC Quantification - Walia, Mayanka; Kumar, Dharmesh; Kumar, Pawan; Singh, Bikram; Padwad, Yogendra S.; Agnihotri, Vijai K. (Planta Medica International Open, 2016)
Potentilla atrosanguinea is well known for its ethnomedicinal uses since ancient times. The present study includes the isolation of a new nortriterpene, 28-methyl-acanthochlamate (1), from the roots of P. atrosanguinea. The structure of 1 was established from HR-ESI-MS and NMR spectroscopic analysis. Its relative stereochemistry was set with the help of NOESY correlation experiment. Compound (1) has been quantified by a new developed UPLC-DAD method (1.1 mg/g). The in vitro cytotoxicity of the new compound (1) was evaluated by sulforhodamine B assay against three cancer cells; human cervical cancer (SiHa), epidermal carcinoma (KB), and human adenocarcinoma (Colo-205). The new isolated compound (1) showed a significantly higher cytotoxicity against all the cells (SiHa, IC50 30.5 µg/mL; KB, IC50 22.6 µg/mL and Colo-205, IC50 18.8 µg/mL).
Keywords: Potentilla atrosanguinea; Rosaceae; 28-methyl-acanthochlamate; quantification; cytotoxicity